All i know about animal behavior i learned in loehmann's dressing room eaudiobook - Bombeck, Erma (Recorded Books Inc., 1995)
America's favorite home humorist, Erma Bombeck, has the uncanny ability to transform the trivialities of everyday American life into rich, witty stories that capture the imagination and tickle the funnybone. In this best-selling collection of hilarious tidbits, she turns her talents to the animal kingdom: the behavioral patterns of the creatures in the wild and the couple in the duplex next door.